A handbook of diction for singers Italian, German, French - Adams, David 1950- (Oxford University Press, 2022)
Featuring updates, expansions, and a new chapter on phonetic symbols and unique sounds in Italian, German, and French, this third edition is a complete guide to achieving professional levels of diction in the three major languages of the classical vocal repertory
This edition also issued in print: 2022. - Previous edition: 2008. - Includes bibliographical references and index
Keywords: Singing / Diction; Italian language / Pronunciation; German language / Pronunciation; French language / Pronunciation; Italienisch; Aussprache; Gesang; Deutsch; Französisch